2021
DOI: 10.1007/s40489-021-00251-0
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Prosocial Behavior in Siblings of Children with Autism Spectrum Disorder: a Systematic Review

Abstract: Siblings of children with ASD have, as a group, more autistic traits than typically developing individuals. A high prevalence of autistic traits may (or may not) include lower scores on measures of empathy and prosocial behavior compared with typically developing individuals. The purpose of this study was to conduct a systematic review of studies of empathy and prosocial behavior in siblings of individuals with ASD. We conducted a comprehensive literature search of studies published until March 2020. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 82 publications
0
1
0
2
Order By: Relevance
“…Una investigación multinacional realizada durante la pandemia Covid 19, encontró que la empatía hacia personas cercanas se convierte en un factor resiliente en situaciones de incertidumbre, la motivación para asistir a la vacunación está influenciada por sentimientos de empatía general relacionada a las necesidades de inmunidad grupal (Butovskaya, et al, 2021). Una revisión sistemática reportó que, en la mayoría de investigaciones sobre la empatía entre familiares respecto a un hermano con trastorno de espectro autista, algunos tienen empatía intacta y presentan comportamiento de apoyo mutuo (Orm et al 2021).…”
Section: Hallazgos Y Problemáticasunclassified
“…Una investigación multinacional realizada durante la pandemia Covid 19, encontró que la empatía hacia personas cercanas se convierte en un factor resiliente en situaciones de incertidumbre, la motivación para asistir a la vacunación está influenciada por sentimientos de empatía general relacionada a las necesidades de inmunidad grupal (Butovskaya, et al, 2021). Una revisión sistemática reportó que, en la mayoría de investigaciones sobre la empatía entre familiares respecto a un hermano con trastorno de espectro autista, algunos tienen empatía intacta y presentan comportamiento de apoyo mutuo (Orm et al 2021).…”
Section: Hallazgos Y Problemáticasunclassified
“…The empathy-altruism hypothesis suggests that when one finds another person in an unfortunate predicament, they will have feelings of empathy and compassion for that person, which elicits the motive and behavior to help others ( Batson, 1987 ). Empirical research has shown that empathy positively predicts prosocial behavior and that the higher level of empathy, the greater attention to the feelings and needs of others, and the more engagement in prosocial behavior ( Van et al, 2018 ; Lindsey and Madera, 2021 ; Marcelo et al, 2021 ; Orm et al, 2021 ). While prior research demonstrates the relationship between empathy and prosocial behavior, researchers to date have mainly focused on children and adolescents, and little is known about how college students’ empathy affect their prosocial behavior ( Zhao et al, 2019 ; Streit et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, diversas investigaciones mencionan que la empatía conduce a una motivación altruista que se traduce en conductas prosociales (Herrera et al, 2018;Kamas & Preston, 2021;Orm et al, 2021), y nuestros hallazgos hacen un aporte a esta teoría a través de juegos multiusuario basados en la ubicación con Realidad Aumentada Móvil implementando dinámicas colaborativas, competitivas y narrativas dirigidos por diálogos.…”
Section: Resultados De Usabilidad Y Experiencia De Juegounclassified